Precificação da energia eólica offshore no Brasil - Medeiros, João Paulo Costa de (2014)
Offshore wind power emits low amounts of gases, is renewable and has better performance than onshore due to its greater stability and higher wind power density, less visual and noise impact, among others. Brazil has a high capacity of generation, but has not yet developed any offshore projects. High costs are a strong impediment. This study is an effort towards pricing offshore resources through Livelized Cost of Energy - LCOE, which represents the minimum return to cover the costs of development, production and maintenance of a wind project. Initially LCOE was calculated for all Brazilian onshore wind farms listed at Bloomberg New Energy Finance R○, accounting for 71 farms. Then hypothetical offshore wind farms were created from the onshore farms, tripling the cost of generation, which is consistent with the literature, and estimating the offshore energy for two locations off the Brazilian coast using satellite data extracted from National Oceanic and Atmospheric Administration. The results demonstrate that offshore resources have the potential to significantly reduce the energy price due to the better performance of the wind at sea